Prove that 0v = 0, for all v in V: I put down: from property 5 and property 8 we know that: v = 1v = (1+0)v = 1v + 0v = v + 0v = v+0 =v. thus, -v+v = -v+(v+0v) = (-v+v) + 0v. He said it was right but not totally right, and to prove it for anything (general case), ,and something about expressing W in terms of v in order to do that. Anyone?
The answer to the question is available in the PDF file https://assignmentexpert.com/https://assignmentexpert.com/homework-answers/mathematics-answer-24223.pdf
Comments
Leave a comment